Assessment of lead and cadmium in the eggs of Gallus gallus in Ibadan, Nigeria (2014)
A study was carried out on the assessment of lead and cadmium in the eggs of Gallus gallus in Agbowo and Oluyole area of Ibadan. The aims and objectives of the study were to assess the level of lead (Pb) and cadmium (Cd), study the relationship between lead and cadmium, study the trend of lead and cadmium levels and estimate the health risk in consuming the eggs. Egg samples were collected randomly and fortnightly between July to September 2013 as rainy season and January to February 2014 as representing dry season. Eggs were acid-digested after weighing out 0.5g using weighing balance. Digested egg parts were then transferred to the Buck Scientific's 210VGP Atomic Absorption Spectrophotometer (AAS) for heavy metal analyses of lead and cadmium. Results show that the mean metal concentration in the eggs were in the order for Pb as: Egg yolk<egg white<egg shell, while Cd was egg yolk<egg shell<egg white in the month of July 2013 in Oluyole, while in Agbowo for the same month was Cd: Egg yolk<egg white<egg shell, while Pb was egg white<egg yolk<egg shell. Similar trends were observable with slight variations for other months and locations, but with the egg shell usually having a higher mean concentration for both metals. The mean seasonal pattern of variation in the heavy metals in the egg parts showed that lead was higher for both seasons than cadmium throughout the study. The rainy season values for cadmium and lead were lower than that of the dry season in both Agbowo and Oluyole areas of Ibadan. In Oluyole, Cd was higher during the rainy season (0.1156ppm) than during the dry season (0.1022ppm) with a similar pattern repeating itself for Pb in the egg shell from Oluyole area. The target hazard quotient (THQ) used for assessing health risk exceeded 1 for both lead and cadmium in the eggs thereby indicating a potential health risk associated with the metals. There was correlation between the occurrence of lead and cadmium in the eggs for all the months and locations thereby indicating a relationship between the two metals. The study shows that eggs supplied in parts of Ibadan are impacted by heavy metals such as lead and cadmium with potential health consequences that needs to further investigated